2021
DOI: 10.1021/acsapm.0c00983
|View full text |Cite
|
Sign up to set email alerts
|

Piezoresistive and Electrical Properties of a Catecholic Amino Acid–Polyacrylamide Single-Walled Carbon Nanotube Hydrogel Hybrid Network

Abstract: We have developed a functional hydrogel combining the advantages of single-walled carbon nanotube (SWCNT) hydrogels and 3,4-dihydroxy-l-phenylalanine (l-DOPA) that would be expected to lead to a material with elevated piezoresistive ability. SWCNT hydrogel precursors were thus embedded into the catecholic amino acid 3,4-dihydroxy-l-phenylalanine–polyacrylamide (l-DOPA-PAM) hydrogel to form a l-DOPA-PAM-SWCNT hydrogel hybrid network. This hybrid network as formed was soft but became a hard gel at room temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Due to the Zr 4+ can react with the carboxyl groups of PAA- g -Dopa to form stable metal coordination at room temperature, the mechanical properties of hydrogels can be controlled by Zr 4+ . Over the past decade of research, researchers have found that the catechol group of Dopa is a key component in adhesion processes. , As shown in Scheme (c), the catechol groups of PAA- g -Dopa enable stick to the various substrates through a range of interactions, including hydrogen bonding, metal coordination, hydrophobic interaction, and other interaction (e.g., π–π electron or cation-π interaction). In detail, for inorganic surfaces, catechol groups could form hydrogen bonds, , p–p electro interaction, and metal–Dopa coordinate bonds .…”
Section: Resultsmentioning
confidence: 99%
“…Due to the Zr 4+ can react with the carboxyl groups of PAA- g -Dopa to form stable metal coordination at room temperature, the mechanical properties of hydrogels can be controlled by Zr 4+ . Over the past decade of research, researchers have found that the catechol group of Dopa is a key component in adhesion processes. , As shown in Scheme (c), the catechol groups of PAA- g -Dopa enable stick to the various substrates through a range of interactions, including hydrogen bonding, metal coordination, hydrophobic interaction, and other interaction (e.g., π–π electron or cation-π interaction). In detail, for inorganic surfaces, catechol groups could form hydrogen bonds, , p–p electro interaction, and metal–Dopa coordinate bonds .…”
Section: Resultsmentioning
confidence: 99%
“…22,128−131 For a mechanical response, in one study, a hybrid network was fabricated combining a single-walled carbon nanotube (SWCNT) hydrogel and a 3,4-dihydroxy-L-phenylalaninepolyacrylamide hydrogel (L-DOPA-PAM). 132 This material has possible utility in pressure sensing applications due to its negative piezoresistive effect, meaning an increase in the stress applied to the material decreases its electrical resistance. Its electrical resistance also decreased over time at a constant applied pressure.…”
Section: Other Stimuli and Multiresponsivementioning
confidence: 99%
“…Furthermore, the piezoresistive effect typically refers to the phenomenon where the resistance of a semiconductor changes due to the variation in energy levels of the conduction band caused by stress-induced band structure changes [101][102][103][104]. However, in the context of hydrogel applications, the piezoresistive effect generally refers to changes in resistance resulting from variations in the dimensions of the gel under deformation [105][106][107][108]. Based on this characteristic, hydrogels can be used for stress or strain sensing.…”
Section: Triboelectric Piezoelectric and Piezoresistive Effectsmentioning
confidence: 99%